2014
DOI: 10.1016/j.jtcvs.2014.06.057
|View full text |Cite
|
Sign up to set email alerts
|

The long-term impact of diabetes on graft patency after coronary artery bypass grafting surgery: A substudy of the multicenter Radial Artery Patency Study

Abstract: The use of the radial artery should be strongly considered in diabetic patients undergoing coronary bypass surgery, especially with high-grade target vessel stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 20 publications
0
39
1
1
Order By: Relevance
“…Diabetes was associated with an increased risk of graft occlusion at 1 year and 7.5 years postoperatively in the RAPS studies [59,60]; however, the use of an RA compared with SV grafting was associated with reduced graft occlusion in the diabetic cohort. In observational studies, the use of an RA as a second arterial conduit proved to be protective in terms of late survival [61,62].…”
Section: Diabetic Patientsmentioning
confidence: 91%
“…Diabetes was associated with an increased risk of graft occlusion at 1 year and 7.5 years postoperatively in the RAPS studies [59,60]; however, the use of an RA compared with SV grafting was associated with reduced graft occlusion in the diabetic cohort. In observational studies, the use of an RA as a second arterial conduit proved to be protective in terms of late survival [61,62].…”
Section: Diabetic Patientsmentioning
confidence: 91%
“…По данным R. Zakeri и соавт., высокий предоперационный уровень креатинина ассоциируется с госпитальной летальностью после КШ [19]. S. Deb с коллегами показали, что повышение креатинина является стойким предиктором окклюзий коронарных шунтов в послеоперационном периоде [20]. Однако более предпочтительной является оценка почечной функции по СКФ, поскольку даже при ее снижении на 75% и более показатели креатинина могут оставаться в пределах нормальных значений [21].…”
Section: скорость клубочковой фильтрацииunclassified
“…Considering the extent and severity of coronary arteries atherosclerosis in people with diabetes, percutaneous intervention (PCI) is usually difficult or even impossible to perform. As a consequence, diabetics are frequently referred to surgical myocardial revascularization, and comprise about 1/3 of patients undergoing coronary artery by-pass grafting (CABG) [4]. It was shown that the risk of HF is increased two- to threefold in people with diabetes, compared with non-diabetic subjects.…”
Section: Introductionmentioning
confidence: 99%